Social skills and the individual wage growth of less educated workers - Philippe Aghion; Antonin Bergeaud; Richard W. Blundell; Rachel Griffith (Institute for Fiscal Studies (IFS), 2024)
Matched employee-employer data from the UK are used to investigate the importance of social skills, in particular team-work and communication with co-workers, as a driver of wage growth for workers with lower formal education. We find that in social skills tasks, workers enjoy greater wage progression with tenure and also accrue higher returns in firms with a higher concentration of more educated colleagues. Additionally, workers exit sooner from jobs where social skills are more important. We rationalize these dynamics through a model that assesses social skills based on complementarity with a firm's assets, where social skills, initially opaque to both the employee and employer, become increasingly appar- ent over time.
Keywords: J31; J24; L25; 330; team work; social skills; tenure-wage profiles; individual wage growth; firm pay premium